Predatory Bacteria in the Treatment of Infectious Diseases and Beyond - Konstantinos Alexakis; Stella Baliou; Petros Ioannou (MDPI AG, 2024)
Antimicrobial resistance (AMR) is an increasing problem worldwide, with significant associated morbidity and mortality. Given the slow production of new antimicrobials, non-antimicrobial methods for treating infections with significant AMR are required. This review examines the potential of predatory bacteria to combat infectious diseases, particularly those caused by pathogens with AMR. Predatory bacteria already have well-known applications beyond medicine, such as in the food industry, biocontrol, and wastewater treatment. Regarding their potential for use in treating infections, several in vitro studies have shown their potential in eliminating various pathogens, including those resistant to multiple antibiotics, and they also suggest minimal immune stimulation and cytotoxicity by predatory bacteria. In vivo animal studies have demonstrated safety and efficacy in reducing bacterial burden in various infection models. However, results can be inconsistent, suggesting dependence on factors like the animal model and the infecting bacteria. Until now, no clinical study in humans exists, but as experience with predatory bacteria grows, future studies including clinical studies in humans could be designed to evaluate their efficacy and safety in humans, thus leading to the potential for approval of a novel method for treating infectious diseases by bacteria.